Harnessing nanoparticles for reshaping tumor immune microenvironment of hepatocellular carcinoma - JinSong Li; GuanBo Zhang; Gang Li; Jie Zhang; Zhi Yang; Lin Yang; ShiJie Jiang; JiaXing Wang (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) is one of the most prevalent cancers, characterized by high morbidity and mortality rates. Recently, immunotherapy has emerged as a crucial treatment modality for HCC, following surgery, locoregional therapies, and targeted therapies. This approach harnesses the body's immune system to target and eliminate cancer cells, potentially resulting in durable antitumor responses. However, acquired resistance and the tumor immunosuppressive microenvironment (TIME) significantly hinder its clinical application. Recently, advancements in nanotechnology, coupled with a deeper understanding of cancer biology and nano-biological interactions, have led to the development of various nanoparticles aimed at enhancing therapeutic efficacy through specific targeting of tumor tissues. These nanoparticles increase the accumulation of immunotherapeutic drugs within the tumor microenvironment, thereby transforming the TIME. In this review, we provide a concise overview of the fundamental principles governing the TIME landscape in HCC and discuss the rationale for and applications of nanoparticles in this context. Additionally, we highlight existing challenges and potential opportunities for the clinical translation of cancer nanomedicines.